KARAKTERISTIK PASIEN TB-MDR DI RSUD CILACAP PERIODE JANUARI - DESEMBER 2017 - Kasron; Edhi Rahayu, Yuni Sapto; Sobirin (MEDIA ILMU KESEHATAN, 2019)
Background: Cilacap General Hospital or RSUD Cilacap is a referral center for patients with multidrug resistance tuberculosis (MDR-TB) in western Central Java (Cilacap, Banyumas, Purbalingga, Brebes, Kebumen, Bumiayu, Banjarnegara). Until now there are still few reports on the characteristics of patients with MDR-TB in hospitalsObjective: To identify the characteristics of MDR TB patients in 2017, such as age, gender, education, working status, criteria suspected, treatment and comorbidities.Methods: This was quantitative research with descriptive design uses a survey approach with document analysis. The sampling technique was total sampling. Research subjects was 68 peoples. Data were analyzed using descriptive statisticResults: The age characteristics of patients 20-40 years 50%, women 58.8%, elementary education 42.6%, non-working 32.4%, suspected relapse criteria 42.6%, still under treatment 72.1% and no comorbidities 70.6%, with comorbid DM 22.1%, HIV 5.9%, CHF 1.5%Conclusion: The characteristics of MDR-TB patients in Cilacap General Hospital are half of patients aged 20-40 years, more than half of women, almost half have elementary school education, almost half do not work, almost half have suspected relapse criteria, most are still in the treatment process and most are not comorbid